The Influence of Working Capital Ratio and Debt Ratio to Rentability at PT. Holcim Indonesia, Tbk for the Period 2010-2019 - Ratna Dumilah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the effect of working capital ratio and debt ratio to profitability at PT. Holcim Indonesia, Tbk. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, the working capital ratio has a significant effect on profitability of 44.3%, the hypothesis test is obtained t count > t table or (2.552 > 2.306). The debt ratio has a significant effect on Rentability of 69.4%, the hypothesis test is obtained t count < t table or (-4.258 < 2.306). Working capital ratios and debt ratios simultaneously have a significant effect on Profitability obtained by the regression equation Y = 24.307 + 0.621X1 - 0.430X2 and a determination value of 96.2%, hypothesis testing obtained a calculated F value > F table or (88.636 > 4,350).